2015
DOI: 10.5812/archneurosci.25066
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Sustained, Selective and Shifting Attention and Behavioral Symptoms in Children With High-Functioning Autism

Abstract: Background:The association of autism symptoms and cognitive abilities can facilitate the etiology and treatment of autism disorders. Destruction of executive functions is one of the several potential cognitive phenotypes in autism. Objectives: The purpose of this study was to investigate the relationship between deficit executive functions and behavioral symptoms in children with high-functioning autism. Materials and Methods:In this cross-sectional study, 50 children with high-functioning autism were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…The study results are consistent with those of Ileto regarding the significant relationship between pragmatic language and behavioral regulation [12]. According to previous studies, impairment in behavioral regulation is considered as the main core of ASD; it causes compatibility and communication problems in this group [6,22]. Blain-Brière et al [6] reported that high inhibition reduced daring and courage.…”
Section: Discussionsupporting
confidence: 89%
“…The study results are consistent with those of Ileto regarding the significant relationship between pragmatic language and behavioral regulation [12]. According to previous studies, impairment in behavioral regulation is considered as the main core of ASD; it causes compatibility and communication problems in this group [6,22]. Blain-Brière et al [6] reported that high inhibition reduced daring and courage.…”
Section: Discussionsupporting
confidence: 89%
“…Cognitive flexibility refers to one's ability to perform different tasks in response to reposition or change one's way of thinking (14). Dysfunction in cognitive flexibility is associated with preservation, stereotypic behaviors, and activity adjustment problems (15) Based on a study by Shiri et al (2015), cognitive flexibility deficit in children with high-functioning autism was significantly correlated with stereotypic behaviors, communication problems, and social interaction symptoms (17). Brian and colleagues found a significant relationship between cognitive flexibility and stereotypic behaviors (13).…”
Section: Cognitive Flexibilitymentioning
confidence: 99%
“…Based on a study by , response inhibition in children with high-functioning autism is correlated with communication and social interactions (17). Brian and colleagues found that behavioral stereotypes are significantly related to response inhibition (13).…”
Section: Response Inhibitionmentioning
confidence: 99%
“…Autism spectrum disorder is a neurodevelopmental disorder associated with communication deficits, repetitive patterns, behaviors, and activities (1). Autism is a lifelong disorder that usually manifests in the first years of life and is sometimes associated with some degree of intellectual disability, characterized by problems in social interactions, communication, stereotyped behaviors, and limited interests (2)(3). The prevalence of autism has increased dramatically in recent years, reaching about 1 in 54 children born in the United States (4).…”
Section: Introductionmentioning
confidence: 99%
“…1 Autism is a lifelong disorder that usually manifests in the first years of life and is sometimes associated with some degree of intellectual disability, characterized by problems in social interactions, communication, stereotyped behaviors, and limited interests. 2 , 3 The prevalence of autism has increased dramatically in recent years, reaching about 1 in 54 children born in the United States. 4 Due to the problems that this disorder causes to children, parents, and society, evaluation and treatment are essential.…”
Section: Introductionmentioning
confidence: 99%